2014
DOI: 10.1126/science.1247407
|View full text |Cite|
|
Sign up to set email alerts
|

An Antifreeze Protein Folds with an Interior Network of More Than 400 Semi-Clathrate Waters

Abstract: When polypeptide chains fold into a protein, hydrophobic groups are compacted in the center with exclusion of water. We report the crystal structure of an alanine-rich antifreeze protein that retains ~400 waters in its core. The putative ice-binding residues of this dimeric, four-helix bundle protein point inwards and coordinate the interior waters into two intersecting polypentagonal networks. The bundle makes minimal protein contacts between helices, but is stabilized by anchoring to the semi-clathrate water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(178 citation statements)
references
References 34 publications
7
160
0
1
Order By: Relevance
“…2(i) and 2(ii)]. 47,48 In contrast, type II and III fish AFPs are nonrepetitive and show an overall globular fold. 49,50 In fish type II AFPs, this fold is stabilized by cysteine residues.…”
Section: Structure Of Ice-binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…2(i) and 2(ii)]. 47,48 In contrast, type II and III fish AFPs are nonrepetitive and show an overall globular fold. 49,50 In fish type II AFPs, this fold is stabilized by cysteine residues.…”
Section: Structure Of Ice-binding Proteinsmentioning
confidence: 99%
“…Despite this lack regularity in the IBS these proteins are able to bind both basal and prism planes. [59][60][61]65 Crystal structures of various AFPs reveal ordered waters associated with the protein IBS, 48,56,58,65 which are thought to play an important role in ice-binding (see Sec. VI E for more details).…”
Section: -58mentioning
confidence: 99%
“…Possibly, the adsorption of PVA onto ice surfaces is promoted via an indirect interaction of clathrate waters hydrogen-bonded to the hydroxyl groups of the polymer, similar to the binding mechanism of antifreeze proteins to ice surfaces. [30][31][32] Further investigation of the specifi c hydration of PVA may shed light on the adsorption mechanism of PVA onto ice surfaces.…”
Section: Implications For the Ice Binding Of Pvamentioning
confidence: 99%
“…When these protein-bound waters contact the quasi-liquid layer at the interface with ice, the two ice-like water arrangements could fuse together and then turn to ice at temperatures in the TH range. Structure-function analyses have shown that AFPs collectively have a variety of different surfaces (ice-binding sites) that can organize water molecules into a clathrate (8,9).…”
mentioning
confidence: 99%